ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN DALAM BELANJA ONLINE DI KOTA SOLOK - Budi Iskandar Harahap; M Nazer; Fery Andrianus (Jurnal TAM (Technology Acceptance Model), 2020)
The development of information technology and the internet has made it easier to transact through web-based shopping sites, often referred to as online shop. The purpose of this study was to determine the effect of perceived benefits, perceived convenience on consumer loyalty with purchasing decisions as an intervening variable. The sample of this research is 400 civil servants in Solok City Government. This study uses the Path Analysis Test to examine the effect between variables in this study. The results showed that the perception of usefulness, perceived ease of use and purchasing decisions had a positive and significant effect on consumer loyalty and perceived benefits, and perceived ease had a positive and significant effect on purchasing decisions.